A formação continuada de professores: contribuições à prática pedagógica com a participação no projeto Arte na Escola - Polo Bauru - Kobosighawa, Nathalia [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present research is focused to art education and continuing education of teachers, through the project Art in the School, which has a pole at Unesp of Bauru. It is known that is right of the teacher to participate in activities that enable your training continues, in the case of the project in question is granted to professor participant access to actions and an extensive educational materials specific to the area of the arts. For this final project, the researcher that participates in the project as voluntary monitors, will point relevant considerations relating to the meetings promoted by Art Project at school during the year of 2017, highlighting your importance and contributions that point to paths that are aimed at the improvement and qualification of the teaching of art in Brazilian schools

A presente pesquisa tem como foco a Arte-Educação e a formação continuada de professores, por meio do Projeto Arte na Escola, o qual possui um Polo na Unesp de Bauru. Sabe-se que é direito do professor participar de atividades que possibilitem sua contínua formação, no caso do projeto em questão é garantido ao professor participante o acesso às ações e um rico material didático específico da área de Arte. Por este trabalho de conclusão de curso, a pesquisadora que participa do projeto como monitora voluntária, apontará considerações referentes aos encontros promovidos pelo Projeto Arte na Escola durante o ano de 2017, destacando sua importância e contribuições que apontam para caminhos que visam a melhoria e qualificação do ensino de Arte nas escolas brasileiras
Keywords: Arte - Estudo e ensino - Bauru; Professores - Formação; Prática pedagógica; Education